Proline-hydroxylated hypoxia-inducible factor 1α (HIF-1α) upregulation in human tumours. - Cameron E Snell (Public Library of Science (PLoS), 2014)
The stabilisation of HIF-α is central to the transcriptional response of animals to hypoxia, regulating the expression of hundreds of genes including those involved in angiogenesis, metabolism and metastasis. HIF-α is degraded under normoxic conditions by proline hydroxylation, which allows for recognition and ubiquitination by the von-Hippel-Lindau (VHL) E3 ligase complex. The aim of our study was to investigate the posttranslational modification of HIF-1α in tumours, to assess whether there are additional mechanisms besides reduced hydroxylation leading to stability. To this end we optimised antibodies against the proline-hydroxylated forms of HIF-1α for use in formalin fixed paraffin embedded (FFPE) immunohistochemistry to assess effects in tumour cells in vivo. We found that HIF-1α proline-hydroxylated at both VHL binding sites (Pro402 and Pro564), was present in hypoxic regions of a wide range of tumours, tumour xenografts and in moderately hypoxic cells in vitro. Staining for hydroxylated HIF-1α can identify a subset of breast cancer patients with poorer prognosis and may be a better marker than total HIF-1α levels. The expression of unhydroxylated HIF-1α positively correlates with VHL in breast cancer suggesting that VHL may be rate-limiting for HIF degradation. Our conclusions are that the degradation of proline-hydroxylated HIF-1α may be rate-limited in tumours and therefore provides new insights into mechanisms of HIF upregulation. Persistence of proline-hydroxylated HIF-1α in perinecrotic areas suggests there is adequate oxygen to support prolyl hydroxylase domain (PHD) activity and proline-hydroxylated HIF-1α may be the predominant form associated with the poorer prognosis that higher levels of HIF-1α confer.